Isolamento de espécies de Candida em pacientes com Candidíase Atrófica Crônica e atividade antimicrobiana de duas espécies de Mikania - Lund, Rafael Guerra (2008)
A great variety of diseases can affect the oral cavity, such as dental caries and candidosis, being the first one considered the most prevalent oral diseases worldwide. The multifactorial and infect-contagious characteristics of dental caries has been established, associated with resident bacterial pathogens of dental biofilm. These microorganisms are responsible by the production of acids and citotoxic products, which could promote the demineralization of dental structure. Currently, Candida infections constitute an important problem in Public Health. Such findings is basically due to the technological advancements of Medicine, increasing in AIDS infection and immune depressed patients in general, using prolonged antimicrobials therapies, which contributes to the microbial disequilibrium. Therefore, the use of efficient antimicrobial agents against pathogenic bacteria and yeasts is an important tool in the control of these infective diseases. Several natural antimicrobial agents are been investigated because of their possible pharmacological properties. Plants of genus Mikania are pointed out as natural products with noticeable antibacterial, antifungicidal, anti-inflammatory and antineoplasic properties. In this study the potential effect of two Mikania species was evaluated (Mikania glomerata Mg e Mikania hirsutissima Mh) using their crude ethanol extracts, based on the ethnobotanics (popular knowledge) and the literature. The test against mutans streptococci was assessed by the determination of Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and inhibition of cell adherence to a glass surface (Adh). Also during a period of one year denture wearer patients with lesions compatible with Chronic Atrophic Candidiasis and assisted in the Center of Diagnosis of Mouth Diseases (CDMD), were investigated. It was applied a questionnaire a questionnaire including the identification of the subject, demographic, medical history and behaviour (oral hygiene and prosthesis wear). It also was carried out a intra-oral exam, where appearance and extension of the stomatitis lesion were evaluated. The microbiological collect was carried out frictioning sterilized swabs in the palate s mucosa, tongue or both of them. The samples were seeded in Agar Sabouraud Dextrose with 100mg/mL of chloramphenicol and they were incubated at 37oC for 24-48h. The presumptive identification of Candida species was based on the morphologic characteristics, Gram colorization of the yeasts, microculture test, hypertonic broth test and it was confirmed by the CHROMagar. The MIC against Streptococcus mutans UA159 was 44.45 Lg/mL (Mg) and 88.90 Lg/mL (Mh), and the MBC was 88.90 Lg/mL (Mh). Against Streptococcus sobrinus 6715, the MIC was 22.23 Lg/mL (Mh) and 88.90 Lg/mL (Mg), and the MBC was 177.80 Lg/mL (Mh). The celular adherence also was inhibited at concentrations of 20 Lg/mL(Mh) and 40 Lg/mL (Mg). These results provide promising baseline information for the potential use of two species of Mikania against mutans streptococci. These findings warrant more-in-depth studies of the active principles of this Mikania ethanol extracts. With regard to Candida isolation with clinical diagnosis of Chronic Atrophic Candidiasis: 1)the results did not confirm a significant difference between patients with clinical diagnosis of denture stomatitis concerning the presence or absence of yeasts; 2) the occurrence of Candida in patients with clinical diagnosis of Chronic Atrophic 6 Candidiasis was negatively related to important factors associated to this opportunistic infection; and 3) mycological findings from the present study do not indicate that the covariates investigated have a significant effect on oral infection by Candida albicans or other species of Candida genus